The geometric contents and the values of local batik in Indonesia - Noerhasmalina Noerhasmalina; Binti Anisaul Khasanah (Jurnal Elemen, 2023)
The culture was carefully associated with regular lifestyles, such as inside the discipline of education. However, there needs to be awareness among school members of the absorption of the culture around them through learning, especially mathematics. Therefore, this study aims to explore the geometric contents in the form of geometric transformations and the values of local batik Indonesia. This study was a qualitative study with an ethnographic approach. The techniques used in this study are observation, literature review, and interviews with Lampung cultural and batik craftsmen. Observations were made by observing batik activities and Lampung batik motifs and conducting interviews to find the mathematical and philosophical elements contained in them. The data were then completed and checked for correctness based on the results from the literature review. The outcomes of this observation imply that the human beings of Lampung utilize the idea of geometric transformation in making batik motifs, which include the Siger motif, pohon hayat motif, and kapal motif. The idea of geometric transformation used is reflection, dilation, and translation. Thus, this research can be a reference for learning mathematics and exploring other Lampung batiks motifs.